Pengaruh Latihan Plyometric dan Lompat Gawang untuk Meningkatkan Kemampuan Jumping Smash pada Siswa Ekstrakulikuler Bola Voli Putri SMP Negeri 2 Karanggayam - Junianto, Heri Is; widodo, Puput (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
This study aims to determine: 1) is there an effect of plyometric jump exercise on the female volleyball athlete's jumping smash at SMP Negeri 2 Karanggayam, 2) is there an effect of goal-jumping exercise on the extracurricular female volleyball athlete's jumping smash at SMP Negeri 2 Karanggayam, 3) the type of exercise used more effective against the jumping smash of female volleyball athletes at SMP Negeri 2 Karanggayam. This research is an experiment with the research design used is